Shalat dan Kesehatan Jasmani - Rofiqoh, Aqidatur (Spiritualita, 2020)
This article is an analytical descriptive study to explore information about the benefits of prayer on physical health.Â  The results of the study show that prayer is not only a spiritual dimension which is often referred to as mi rÄj al-mu' min.Â  However, prayer is also of beneficial value for the physical health of the doer.Â  These benefits, among others, are obtained through prayer movements, starting with Takbirah al-IhrÃ¢m, followed by bowing, i'tidal, prostration, and sitting, then ending with a greeting.Â  These findings suggest that prayer is not merely an obligation, as a form of worship to Allah.Â  More than that, prayer is a necessity.Â  Thus, leaving prayer does not only mean abandoning one's obligations but also means not fulfilling one's needs.